Donald Rumsfeld papers - Rumsfeld, Donald, 1932-
Correspondence, memoranda, minutes, speeches, writings, reports, notes, testimony, interviews, oral histories, briefing books, statements, cables, agendas, appointment and scheduling files, confirmation hearings, legislative files, polls, campaign files, constituent casework and issue mail, service academy appointment files, press releases, newsletters, financial records, family papers, genealogies, news clippings, printed matter, memorabilia, photographs, and other papers concerning Rumsfeld's service as U.S. representative from Illinois, White House official, U.S. secretary of defense, U.S. ambassador to the North Atlantic Treaty Organization, and chair of various public commissions. Also documents his activities in the private sector including executive positions and board memberships in corporate businesses and nonprofit organizations.
Documents Rumsfeld's role in the Richard M. Nixon administration as personal assistant and counselor to the president, director of the U.S. Cost of Living Council and U.S. Office of Economic Opportunity; Gerald R. Ford administration as chief of staff and U.S. secretary of defense; in the Ronald Reagan administration as special presidential envoy to the Middle East; and in the George W. Bush administration as U.S. secretary of defense.
Includes material pertaining to the Economic Stabilization Program; House Republican Conference; National Economic Commission; United States-Japan Advisory Commission; U.S. Agency for International Development and nonmilitary spending in Vietnam; U.S. Commission to Assess National Security Space Management and Organization; U.S. Commission to Assess the Ballistic Missile Threat to the United States; U.S. Congress House Committee on Government Operations; U.S. Congress House Committee on Science and Astronautics; U.S. Congress Joint Economic Committee; U.S. National Aeronautics and Space Administration, U.S. space program, Project Apollo accident, and military use of space technology; U.S. Selective Service System reform; U.S. Trade Deficit Review Commission; U.S. Freedom of Information Act; and U.S. Legislative Reorganization Act and congressional reform. Includes a small chronological file relating to the wars in Afghanistan and Iraq. Subjects include civil rights; domestic issues; foreign affairs; Illinois state politics; Latin America; law of the sea; national security; terrorism; presidential elections, 1981-2003; the President's Club, Lyndon B. Johnson, and campaign funding: Republican Party politics; urban affairs; Vietnam War; and weapons of mass destruction.
Documents Rumsfeld's work as chief executive officer of the pharmaceutical company G.D. Searle & Co. and of General Instrument Corporation. Also documents Rumsfeld's work with ABB Asea Brown Boveri; Amylin Pharmaceuticals; Eisenhower fellowships; Gilead Sciences; National Park Foundation; Rand Corporation; Sears, Roebuck and Company; and the Tribune Company.
Correspondents include Kenneth L. Adelman, William F. Buckley, George Bush, George W. Bush, Frank Charles Carlucci, Richard B. Cheney, Marguerite Stitt Church, Everett McKinley Dirksen, Gerald R. Ford, Newt Gingrich, Alexander Meigs Haig, Henry Kissinger, Daniel P. Moynihan, John E. Moss, Richard M. Nixon, Charles H. Percy, Shimon Peres, Brent Scowcroft, and George Pratt Shultz.
Microfilm of selected files from Parts I and II (filmed prior to arrangement of the Donald Rumsfeld Papers by the Library of Congress Manuscript Division) available
Microfilm produced from originals now in the Manuscript Division.
U.S. secretary of defense, U.S. representative from Illinois, White House official, ambassador, and business executive. Full name: Donald Henry Rumsfeld.
Collection material in English.
Keywords: Adelman, Kenneth L. -- 1946- -- Correspondence; Buckley, William F. -- 1925-2008 -- Correspondence; Bush, George, -- 1924- -- Correspondence; Bush, George W. -- 1946-; Bush, George W. -- 1946- -- Correspondence; Carlucci, Frank Charles, -- 1930- -- Correspondence; Cheney, Richard B. -- Correspondence; Church, Marguerite Stitt, -- 1892-1990 -- Correspondence; Dirksen, Everett McKinley -- Correspondence; Ford, Gerald R., -- 1913-2006.; Ford, Gerald R., -- 1913-2006 -- Correspondence; Gingrich, Newt -- Correspondence; Haig, Alexander Meigs, -- 1924-2010 -- Correspondence; Johnson, Lyndon B. -- 1908-1973.; Kissinger, Henry, -- 1923- -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Moss, John E. -- 1913- -- Correspondence; Nixon, Richard M. -- 1913-1994.; Nixon, Richard M. -- 1913-1994 -- Correspondence; Percy, Charles H., -- 1919- -- Correspondence; Peres, Shimon, -- 1923- -- Correspondence; Reagan, Ronald; Scowcroft, Brent -- Correspondence; Shultz, George Pratt, -- 1920- -- Correspondence; United States. -- Agency for International Development; United States. -- Commission to Assess National Security Space Management and Organization; United States. -- Commission to Assess the Ballistic Missile Threat to the United States; United States. -- Congress -- Reform; United States. -- Congress. -- House; United States. -- Congress. -- House. -- Committee on Government Operations; United States. -- Congress. -- House. -- Committee on Science and Astronautics; United States. -- Congress. -- Joint Economic Committee; United States. -- Cost of Living Council; United States. -- Dept. of Defense; United States. -- National Aeronautics and Space Administration; United States. -- Office of Economic Opportunity; United States. -- Selective Service System; United States; United States; ABB Asea Brown Boveri Ltd; Amylin Pharmaceuticals; Economic Stabilization Program; G.D. Searle & Co; General Instrument Corporation; Gilead Sciences (Firm); House Republican Conference (U.S.); National Economic Commission (U.S.); National Park Foundation; North Atlantic Treaty Organization; President's Club; Rand Corporation; Republican Party (U.S. : 1854- ); Sears, Roebuck and Company; Tribune Company; United States-Japan Advisory Commission; U.S. Trade Deficit Review Commission; White House (Washington, D.C.); Astronautics and state -- United States; Astronautics, Military -- United States; Balance of trade -- United States